Implementasi Cloud Native dan Multi Cloud Pada Sistem Operasi Windows Dengan Menggunakan Docker dan Cara Penggunaannya - Rahman, Rakhmadi; Syaddad, Muhammad Shadiq Dzakwan; Sesa, Velita Rante (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the modern computing era, cloud native and multi-cloud strategies are essential for organizations to increase flexibility, scalability, and operational efficiency. Docker, as a popular containerization platform, becomes the main foundation in the implementation of these two strategies. This research aims to explore the optimization of Windows operating systems in supporting the implementation of Docker for cloud native and Windows Server for multi-cloud. Cloud native is an approach to building and running applications designed specifically for the cloud, which utilizes automation, scalability, and efficient management. Meanwhile, multi-cloud is a strategy that uses a variety of cloud services from different providers to increase reliability, availability, flexibility, and innovation while reducing costs.